Photo-thermal composite curing glass coating composition and preparation method and coating thereof
By using photothermal composite curing technology in the coating, combined with cation and radical polymerization mechanisms, an interpenetrating network structure is formed, which solves the problem of reduced adhesion caused by volume shrinkage during the coating curing process, and achieves excellent water and chemical resistance on glass substrates.
Patent Information
- Application Number
- CN202411809963.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-14
AI Technical Summary
The existing radiation curing coatings shrink greatly during the curing process, resulting in increased stress in the coating, reduced adhesion, and even cracking or falling off. Especially on glass substrates, they are poor boiling resistance and chemical resistance.
The photothermal composite cured glass coating composition is used to form an interpenetrating network structure by combining the two polymerization mechanisms of cation and free radicals, reducing the curing shrinkage rate, improving adhesion and water resistance.
Excellent adhesion, flexibility and blister resistance on glass substrates are achieved, highly soaked and boiled, reducing volume shrinkage during curing and improving the overall performance of the coating.
Smart Images

Figure BDA0005180318740000021 
Figure BDA0005180318740000031 
Figure BDA0005180318740000041
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of coatings, and in particular to a photothermal composite curing glass coating composition and a preparation method and coating thereof. Background Art
[0002] Radiation curing has the advantages of fast curing speed, simple process, and green environmental protection. It is widely used in coatings, adhesives, 3D printing and other fields. Most radiation curing systems are still acrylate systems, which are characterized by large curing shrinkage. The high shrinkage during the curing process will cause internal stress in the coating or adhesive components, reduce the bonding strength, and even cause local cracking and warping. Therefore, reducing or even eliminating the volume shrinkage during the curing process is of great significance to improving the bonding strength of the coating or adhesive.
[0003] The surface energy of the glass substrate is low, the surface is smooth and non-porous, and glass is an inorganic material with high hardness. If the organic polymer coating shrinks greatly during the curing process, it will lead to large stress inside the coating, reduced adhesion and even cracking or falling off of the coating, which is mainly reflected in poor water boiling resistance and poor chemical resistance. This is the main problem of glass coatings. Summary of the invention
[0004] In order to solve the above technical problems existing in the prior art, the present invention provides a photothermal composite curing glass coating composition and a preparation method and coating thereof.
[0005] The technical solution of the present invention to solve the above technical problems is as follows:
[0006] The first aspect of the present invention is to provide a photothermal composite curing glass coating composition, including epoxy resin, epoxy toughener, acrylate monomer, diluent, acrylate crosslinking agent, cationic photoinitiator, free radical photoinitiator, coupling agent, sensitizer and other additives.
[0007] The above technical solution provided by the present invention is a photothermal composite curing composition containing both a cationic system and a free radical system, which is a mixture of monomers, oligomers and initiators of free radical and cationic polymerization mechanisms. Through the coordination of the various components, it can undergo both free radical polymerization and cationic polymerization, and forms an interpenetrating network during the curing process. When used as a glass coating, it has excellent adhesion, flexibility, and resistance to blistering, high alcohol blistering, and boiling.
[0008] On the basis of the above technical solution, the present invention can also make the following improvements:
[0009] Furthermore, the content of each component is as follows, calculated by mass: 40-80 parts of epoxy resin, 10-30 parts of epoxy toughener, 10-30 parts of acrylate monomer, 5-20 parts of diluent, 0-15 parts of acrylate crosslinker, 0.2-5 parts of cationic photoinitiator, 0.4-5 parts of free radical photoinitiator, 0-5 parts of coupling agent, 0.2-3 parts of sensitizer, and 0-2 parts of other additives.
[0010] The beneficial effect of adopting the above further technical solution is that by rationally designing the ratio of each component, the crosslinking degree of the composition is further improved, thereby improving the comprehensive performance of the product.
[0011] Furthermore, the epoxy resin is any one or more of alicyclic epoxy resin, modified alicyclic epoxy resin, hydrogenated bisphenol A epoxy resin, bisphenol A epoxy resin or bisphenol F epoxy resin.
[0012] Further, the alicyclic epoxy resin is selected from any one or more of the following compounds:
[0013]
[0014] The modified alicyclic epoxy resin is a divalent fatty alcohol modified alicyclic epoxy resin or a fatty acid modified alicyclic epoxy resin.
[0015] Furthermore, the epoxy toughening agent includes epoxy toughening agent A and epoxy toughening agent B. In terms of parts by mass, the epoxy toughening agent A is 5-30 parts, and the epoxy toughening agent B is 0-15 parts.
[0016] The epoxy toughening agent A is a glycidyl ether, including any one or more of the following compounds: ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, dipropylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, butanediol diglycidyl ether, neopentyl glycol diglycidyl ether, hydrogenated bisphenol A glycidyl ether, hexanediol diglycidyl ether, cyclohexanedimethanol diglycidyl ether, cyclohexanediol diglycidyl ether, and carbon twelve to fourteen alkyl glycidyl ether; the epoxy toughening agent B is a nano core-shell rubber, the core layer is a rubber elastomer, the outer shell layer is an epoxy resin, the rubber elastomer is polybutadiene rubber, nitrile rubber or silicone rubber, and the epoxy resin of the outer shell layer is an alicyclic epoxy resin, bisphenol A epoxy resin or bisphenol F epoxy resin.
[0017] Further, the acrylate monomer is a mixture of a multifunctional pure acrylate monomer and epoxy acrylate, wherein the multifunctional pure acrylate monomer includes any one or more of pentaerythritol triacrylate, pentaerythritol tetraacrylate, dipentaerythritol pentaacrylate, dipentaerythritol hexaacrylate, hexanediol diacrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, neopentyl glycol diacrylate, neopentyl glycol diethoxy diacrylate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated glycerol triacrylate, and propoxylated trimethylolpropane triacrylate, and the epoxy acrylate is selected from any one or more of the following compounds:
[0018]
[0019] Wherein, R1 and R are independently selected from any one or more of an ester group, an ether bond, a carbonyl group, an aromatic group, and a fatty chain segment.
[0020] Furthermore, the acrylate crosslinking agent includes tetrahydrofuran acrylate, glycidyl methacrylate and any one or more of the following compounds:
[0021]
[0022] Furthermore, the diluent is any one or more of polyols, hydroxyl-terminated acrylates, hydroxyl-terminated vinyl ethers or oxetanes.
[0023] The polyols are any one or more of propylene glycol, butylene glycol, hexylene glycol, polypropylene glycol, polyethylene glycol, polytetramethylene glycol, polycaprolactone, hydroxyl-terminated polyester, polycarbonate diol, polyether polyol, modified castor oil diol, and diethylene glycol; the hydroxyl-terminated acrylate is any one or more of hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, and hydroxybutyl (meth)acrylate.
[0024] The cationic photoinitiator is any one or more of sulfonium hexafluoroantimonate, sulfonium hexafluorophosphate, iodonium hexafluorophosphate, and iodonium hexafluoroantimonate.
[0025] The free radical photoinitiator is at least one of isopropylthioxanthone, 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenylpropanone, and methyl benzoylformate.
[0026] The sensitizer is coumarin or anthracene.
[0027] The coupling agent is any one or more of an epoxy phosphate coupling agent, a silane coupling agent, a titanate coupling agent, an aluminate coupling agent or an aluminum-titanium composite coupling agent.
[0028] The other additives include wetting and leveling agents, defoaming agents, and thixotropic agents.
[0029] The second aspect of the present invention is to provide a method for preparing the above-mentioned light-heat composite curing glass coating composition, comprising the following steps:
[0030] (1) stirring epoxy resin, epoxy toughening agent and diluent at 50-70° C. until uniformly mixed, cooling and setting aside;
[0031] (2) adding an acrylic acid ester monomer and an acrylic acid ester crosslinking agent to the solution obtained in step (1), stirring the mixture evenly at room temperature, and setting aside;
[0032] (3) Adding a cationic photoinitiator, a free radical photoinitiator, a coupling agent, a sensitizer and other additives to the solution obtained in step (2) under light-proof conditions, stirring at room temperature until uniform, and degassing to obtain the photothermal composite curing glass coating composition.
[0033] Another aspect of the present invention is to provide a coating, comprising the above-mentioned photothermal composite curing glass coating composition, wherein the coating is applied to a glass substrate.
[0034] Compared with the prior art, the present invention has the following technical effects:
[0035] The photothermal composite curing glass coating composition provided by the present invention is a cationic polymerization and free radical photothermal curing system, and an acrylic resin for free radical polymerization and an epoxy resin for cationic ring-opening polymerization are mixed to form a free radical-cationic mixed curing system, which combines the advantages of the two polymerization mechanisms and has the advantages of fast curing rate, deep curing degree, no influence of oxygen, and low curing shrinkage, so that the glass coating composition has excellent glass substrate adhesion, flexibility, and water boiling and blister resistance, and the comprehensive performance of the curing system is improved;
[0036] The present invention makes full use of the epoxy groups in the epoxy resin structure to complete the curing through the UV cationic ring-opening reaction, and the curing reaction is not affected by oxygen, the curing shrinkage is small, and the curing can continue after the light stops, and there is a characteristic of dark reaction. Heating further improves the degree of reaction. By adopting a light-heat composite curing method, the resin reaction degree is high, and a relatively complete cross-linking network can be formed, which has excellent adhesion and surface hardness, reduces the influence of incomplete light curing on adhesion and chemical resistance, and has an important influence on improving the overall performance of the coating;
[0037] The reaction stress is fully released, the mechanical properties and adhesion are better, and there will be no problems such as cracking and blistering;
[0038] The main resin in the composition of the present invention adopts alicyclic epoxy resin and modified alicyclic epoxy resin, and the alicyclic epoxy group has good photocuring activity and forms a COC cross-linking network after ring opening, with high cross-linking density and good heat resistance and chemical resistance;
[0039] The acrylate raw materials in the composition of the present invention include acrylate resin, diluent and acrylate crosslinking agent; the main body of the acrylate resin is epoxy-modified acrylate, which has the characteristics of fast free radical curing speed, and contains tough segments and hydroxyl polar groups in the structure, giving the coating toughness and excellent adhesion; the diluent is terminal hydroxyl (methyl) acrylate, one end of which contains a (methyl) acrylate group and the other end contains a hydroxyl group, the substrate wetting effect is good, and not only can it participate in free radical polymerization, but the hydroxyl group can also participate in cationic curing in the form of chain transfer, which can improve the toughness and adhesion of the product; the acrylate crosslinking agent is a monomer containing a (methyl) acrylate group at one end and an epoxy group at the other end, which provides crosslinking points for the cationic curing network and the free radical curing network, so that the coating forms a denser interpenetrating network with excellent performance. DETAILED DESCRIPTION
[0040] The following specific embodiments illustrate the implementation of the present invention, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. Although the description of the present invention will be introduced in conjunction with the preferred embodiment, this does not mean that the features of this invention are limited to this implementation. On the contrary, the purpose of introducing the invention in conjunction with the implementation is to cover other options or modifications that may extend based on the claims of the present invention. In order to provide a deep understanding of the present invention, the following description will include many specific details. The present invention can also be implemented without using these details. In addition, in order to avoid confusion or blurring the focus of the present invention, some specific details will be omitted in the description. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
[0041] Example 1
[0042] The photothermal composite curing glass coating composition includes the following components by mass: 50 parts of 3,4-epoxycyclohexylcarboxylic acid-3',4'-epoxycyclohexyl methyl ester (Yantai Donghua DE021E), 10 parts of special polyether resin (HM210), 10 parts of solid epoxy resin E20 (Changchun Chemical), 5 parts of 3-ethyl-3-oxabutane methanol (Yantai Donghua DE 101), 15 parts of (3-(2-(acryloyloxy)ethoxy)-4-hydroxycyclohexyl)methyl 3-(2-acryloyloxy)ethyl)-4-hydroxycyclohexane-1-carboxylate (Yantai Donghua DR3214, 30% tripropylene glycol diacrylate), 5 parts of glycidyl methacrylate, 5 parts of hydroxyethyl acrylate, 4 parts of hexafluoroantimonate sulfonium salt UVI 6976 (Nantong Synasia), 2 parts of initiator 1173, 0.5 parts of initiator ITX, 0.5 parts of sensitizer PSS 510, 2 parts of silane coupling agent KH-560, 0.5 parts of defoamer BYK A530, 0.3 parts of leveling agent BYK 333;
[0043] Curing process: LED 395nm 15m / min, 180℃ 10min.
[0044] Example 2
[0045] The photothermal composite curing glass coating composition includes the following components by mass: 40 parts of 3,4-epoxycyclohexylcarboxylic acid-3',4'-epoxycyclohexyl methyl ester modified epoxy (Yantai Donghua New Materials Co., Ltd., DE1701), 20 parts of hydrogenated bisphenol A type epoxy resin, 5 parts of bis((3,4-epoxycyclohexyl)methyl) adipate (Nantong Synasia S-28), 25 parts of (3-(2-(acryloyloxy)ethoxy)-4-hydroxycyclohexyl )methyl 3-(2-acryloyloxy)ethyl)-4-hydroxycyclohexane-1-carboxylate (Yantai Donghua DR3215, 15% hexanediol diacrylate), 2 parts of glycidyl methacrylate, 3 parts of epoxycyclohexyl methyl methacrylate (Nantong Synasia S-100), 5 parts of hydroxybutyl acrylate, 5 parts of 1,2-propylene glycol, 4 parts of iodonium hexafluoroantimonate DH002 (Yantai Donghua), 2 parts of initiator 1173, 0.3 parts of sensitizer PSS 510 (Qiangli New Materials), 2 parts of silane coupling agent KH-560, 0.5 parts of defoamer BYK A530, 0.3 parts of leveling agent BYK 333;
[0046] Curing process: LED 395nm 15m / min, 180℃ 10min.
[0047] Example 3
[0048] The photothermal composite curing glass coating composition includes the following components by mass: 30 parts of 3,4-epoxycyclohexylcarboxylic acid-3',4'-epoxycyclohexyl methyl ester modified epoxy (Yantai Donghua New Materials Co., Ltd., DE1601), 20 parts of bisphenol A type epoxy resin (Nanya 128 resin), 25 parts of bisphenol A type epoxy modified acrylate (Sanmu SM 6104), 10 parts of hydroxyethyl acrylate, 5 parts of 3-ethyl-3-oxabutane methanol (Nantong Synasia S-101), 10 parts of special polyether resin (HM6335), 4 parts of hexafluoroantimonate sulfonium salt UVI 6976 (Nantong Synasia), 2 parts of initiator 184, 0.5 parts of initiator ITX, 0.5 parts of sensitizer PSS306 (Qiangli New Material), 2 parts of silane coupling agent KH-560, 2 parts of silane coupling agent KH-570, 0.5 parts of defoamer BYK 066N, 0.3 parts of leveling agent BYK 310;
[0049] Curing process: LED 395nm 15m / min, 180℃ 10min.
[0050] Example 4
[0051] The photothermal composite cured glass coating composition includes the following components by mass: 35 parts of 3,4-epoxycyclohexylcarboxylic acid-3',4'-epoxycyclohexyl methyl ester modified epoxy (Yantai Donghua New Materials Co., Ltd., DE1601), 20 parts of bisphenol A type epoxy resin (Nanya 128 resin), 10 parts of bisphenol A type epoxy modified acrylate (Sanmu SM 6104), 15 parts of (3-(2-(acryloyloxy)ethoxy)-4-hydroxycyclohexyl)methyl 3-(2-acryloyloxyoxy)ethyl)-4-hydroxycyclohexane-1-carboxylate (Yantai Donghua DR3214, 30% tripropylene glycol diacrylate), 5 parts of hydroxyethyl acrylate, 2 parts of diethylene glycol, 3 parts of 1,2-propylene glycol, 5 parts of nano core-shell rubber MX554 (Zhongyuan), 4 parts of hexafluoroantimonate sulfonium salt UVI 6976 (Nantong Synasia), 2 parts of initiator 1173, 0.5 parts of initiator ITX, 0.3 parts of sensitizer PSS 303 (Qiangli New Material), 2 parts of silane coupling agent KH-560, 2 parts of silane coupling agent KH-570, 0.5 parts of defoamer BYK 066N, 0.3 parts of leveling agent BYK 310.
[0052] Curing process: LED 395nm 15m / min, 180℃ 10min.
[0053] Comparative Example 1
[0054] 80 parts of 3,4-epoxycyclohexylcarboxylic acid-3',4'-epoxycyclohexyl methyl ester (Yantai Donghua DE 021E), 20 parts of 3-ethyl-3-oxetane methanol (Yantai Donghua DE 101), 4 parts of hexafluoroantimonate sulfonium salt UVI 6976 (Nantong Synasia), 0.5 parts of sensitizer PSS 306 (Qiangli New Materials), 1 part of silane coupling agent KH-560, 0.5 parts of BYK A530, and 0.3 parts of BYK333.
[0055] Curing process: LED 395nm 10m / min, 180℃ 10min.
[0056] Comparative Example 2
[0057] 45 parts of 3,4-epoxycyclohexylcarboxylic acid-3',4'-epoxycyclohexyl methyl ester modified epoxy (Yantai Donghua New Materials Co., Ltd., DE1601), 20 parts of bisphenol A type epoxy resin (Nanya 128 resin), 25 parts of dipentaerythritol pentaacrylate, 3 parts of glycidyl methacrylate, 2 parts of hydroxypropyl acrylate, 5 parts of nano core-shell rubber MX554 (Zhongyuan), 4 parts of hexafluoroantimonate sulfonium salt UVI 6976 (Nantong Xinashi), 2 parts of initiator 1173, 0.5 parts of initiator ITX, 0.3 parts of sensitizer PSS 303 (Qiangli New Materials), 2 parts of silane coupling agent KH-560, 2 parts of silane coupling agent KH-570, 0.5 parts of defoamer BYK 066N, 0.3 parts of leveling agent BYK 310.
[0058] Curing process: LED 395nm 15m / min, 180℃ 10min.
[0059] Comparative Example 3
[0060] 50 parts of 3,4-epoxycyclohexylcarboxylic acid-3',4'-epoxycyclohexyl methyl ester (Yantai Donghua DE 021E), 15 parts of solid epoxy resin E20 (Changchun Chemical), 10 parts of bisphenol F type epoxy resin NPEF170 (Nanya Chemical), 20 parts of bisphenol A type epoxy modified acrylate (Sanmu SM 6104), 5 parts of glycidyl methacrylate, 4 parts of hexafluoroantimonate sulfonium salt UVI 6976 (Nantong Synasia), 2 parts of initiator 1173, 0.5 parts of initiator ITX, 2 parts of silane coupling agent KH-560, 0.5 parts of defoamer BYKA530, 0.3 parts of leveling agent BYK 333;
[0061] Curing process: LED 395nm 15m / min, 180℃ 10min.
[0062] Performance Testing
[0063] Adhesion test: 100-grid method, substrate: glass sheet, test standard GB / T 9286-2021;
[0064] Water resistance test: Adhesion is tested after soaking in tap water for 2 weeks at 25°C, test standard GB / T9286-2021;
[0065] Alcohol resistance test: At 25°C, test the adhesion after soaking in 55-degree alcohol for 24 hours, test standard GB / T9286-2021;
[0066] Boiling resistance: Adhesion is tested after boiling water at 100℃ / 2h, test standard GB / T 9286-2021;
[0067] Moisture and heat resistance: Adhesion is tested after 2 weeks of treatment at 85℃ / 85%RH, test standard GB / T9286-2021;
[0068] UV aging test: QUV, ASTM G154 Cycle1, colorimetric Lab test, calculation of Δb;
[0069] Heat aging test: oven 180℃ / 1h, colorimetric Lab test, calculate Δb;
[0070] Chromaticity test: Test equipment: HunterLab Ultrascan VIS.
[0071] The performance data of each embodiment and comparative example are shown in Table 1.
[0072] Table 1 Performance data of embodiments and comparative examples
[0073]
[0074]
[0075] From the experimental results in Table 1, it can be seen that the cationic free radical photothermal curing composition coating of the present invention has excellent adhesion and moisture and heat resistance and water boiling resistance, and has excellent weather resistance and temperature yellowing resistance in accelerated aging tests. The viscosity of the composition of the present invention is adjustable, and is 100-10000 centipoise. The composition is suitable for roller coating and screen printing processes. When used in coating formulation, the composition has good substrate wettability and low chroma. After being cured, the composition is colorless and transparent, has low chroma, and has a yellowness YIE 313≤1, does not affect the base color of the substrate, and has excellent temperature yellowing resistance. After being cured, the composition has excellent bonding performance and excellent adhesion to glass substrates (float glass, tempered glass, embossed glass, etc.), and the cross-grid test is 5B. The composition also has excellent water resistance, and the adhesion is 5B after being boiled in 100°C boiling water for 2 hours, and the adhesion is 5B after being soaked in tap water for 2 weeks. The composition has excellent moisture and heat resistance, and the adhesion is 4-5B after being treated at 85°C / 85%RH for 2 weeks. The composition also has excellent alcohol resistance, and the adhesion is 5B after being soaked in 55-degree alcohol for 24 hours.
[0076] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A photothermal composite curing glass coating composition, characterized in that: Including epoxy resin, epoxy toughener, acrylate monomer, diluent, acrylate crosslinking agent, cationic photoinitiator, free radical photoinitiator, coupling agent, sensitizer and other additives.
2. The photothermal composite curing glass coating composition according to claim 1, characterized in that: The content of each component is as follows by mass: 40-80 parts of epoxy resin, 10-30 parts of epoxy toughening agent, 10-30 parts of acrylate monomer, 5-20 parts of diluent, 0-15 parts of acrylate crosslinking agent, 0.2-5 parts of cationic photoinitiator, 0.4-5 parts of free radical photoinitiator, 0-5 parts of coupling agent, 0.2-3 parts of sensitizer, and 0-2 parts of other additives.
3. The photothermal composite curing glass coating composition according to claim 1 or 2, characterized in that: The epoxy resin is any one or more of alicyclic epoxy resin, modified alicyclic epoxy resin, hydrogenated bisphenol A epoxy resin, bisphenol A epoxy resin or bisphenol F epoxy resin.
4. The photothermal composite curing glass coating composition according to claim 3, characterized in that: The alicyclic epoxy resin is selected from any one or more of the following compounds: The modified alicyclic epoxy resin is a divalent fatty alcohol modified alicyclic epoxy resin or a fatty acid modified alicyclic epoxy resin.
5. The photothermal composite curing glass coating composition according to claim 1 or 2, characterized in that: The epoxy toughening agent comprises epoxy toughening agent A and epoxy toughening agent B. In terms of weight percentage, the epoxy toughening agent A is 5-30 parts, and the epoxy toughening agent B is 0-15 parts.
6. The photothermal composite curing glass coating composition according to claim 1 or 2, characterized in that: The acrylate monomer is a mixture of a multifunctional pure acrylate monomer and epoxy acrylate, wherein the multifunctional pure acrylate monomer includes any one or more of pentaerythritol triacrylate, pentaerythritol tetraacrylate, dipentaerythritol pentaacrylate, dipentaerythritol hexaacrylate, hexanediol diacrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, neopentyl glycol diacrylate, neopentyl glycol diethoxy diacrylate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated glycerol triacrylate, and propoxylated trimethylolpropane triacrylate, and the epoxy acrylate is selected from any one or more of the following compounds: Wherein, R1 and R are independently selected from any one or more of an ester group, an ether bond, a carbonyl group, an aromatic group, and a fatty chain segment.
7. The photothermal composite curing glass coating composition according to claim 1 or 2, characterized in that: The acrylate crosslinking agent includes tetrahydrofuran acrylate, glycidyl methacrylate and any one or more of the following compounds:
8. The photothermal composite curing glass coating composition according to claim 1 or 2, characterized in that: The diluent is any one or more of polyols, hydroxyl-terminated acrylates, hydroxyl-terminated vinyl ethers or oxetanes.
9. A method for preparing the photothermal composite curing glass coating composition according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) stirring epoxy resin, epoxy toughening agent and diluent at 50-70° C. until uniformly mixed, cooling and setting aside; (2) adding an acrylic acid ester monomer and an acrylic acid ester crosslinking agent to the solution obtained in step (1), stirring the mixture evenly at room temperature, and setting aside; (3) Adding a cationic photoinitiator, a free radical photoinitiator, a coupling agent, a sensitizer and other additives to the solution obtained in step (2) under light-proof conditions, stirring at room temperature until uniform, and degassing to obtain the photothermal composite curing glass coating composition.
10. A coating, characterized in that: The invention comprises the light-heat composite curing glass coating composition according to any one of claims 1 to 8, wherein the coating is applied to a glass substrate.
Citation Information
Patent Citations
tobacco pipe
DE321430A